2019
DOI: 10.1515/nanoph-2018-0217
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth-based metamaterials: from narrowband reflective color filter to extremely broadband near perfect absorber

Abstract: In recent years, sub-wavelength metamaterials-based light perfect absorbers have been the subject of many studies. The most frequently utilized absorber configuration is based on nanostructured plasmonic metals. However, two main drawbacks were raised for this design architecture. One is the fabrication complexity and large scale incompatibility of these nano units. The other one is the inherent limitation of these common metals which mostly operate in the visible frequency range. Recently, strong interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 70 publications
(48 reference statements)
0
33
0
Order By: Relevance
“…Even using a larger number of [MI] N pairs (e.g., 16 pairs) cannot significantly substantiate the BW [32]. In a recent article, our group revealed an extraordinary optical response of bismuth (Bi) metal in lightperfect absorption [46]. We experimentally demonstrated a near-unity average absorption from 500 to 2,500 nm, which is the largest reported BW for a planar MI pair-based design to date.…”
Section: Lithography-free Multilayer Perfect Absorbersmentioning
confidence: 83%
See 1 more Smart Citation
“…Even using a larger number of [MI] N pairs (e.g., 16 pairs) cannot significantly substantiate the BW [32]. In a recent article, our group revealed an extraordinary optical response of bismuth (Bi) metal in lightperfect absorption [46]. We experimentally demonstrated a near-unity average absorption from 500 to 2,500 nm, which is the largest reported BW for a planar MI pair-based design to date.…”
Section: Lithography-free Multilayer Perfect Absorbersmentioning
confidence: 83%
“…To reduce the angle sensitivity of the absorption response, ZnO with a refractive index of 1.9 was applied as an insulator layer. We further improved RGB color-generation efficiency by employing a Bi-based MIMI filter [46]. It was theoretically and experimentally shown that the structure composed of Al-LiF-Bi-LiF layers can create additive RGB colors with an amplitude as large as 0.9.…”
Section: Filteringmentioning
confidence: 99%
“…Different metal–insulator combinations were utilized to obtain ultrabroadband light absorption from these multilayer designs. W‐Al 2 O 3 , Cr‐SiO 2 , W‐SiO 2 , Mo‐SiO 2 , Ag‐Si, Bi‐LiF, and Ni‐SiO 2 are some examples of these MI pairs to obtain perfect broadband absorption. Further improvements can be also achieved using different strategies; excitation of multiple modes in a multithickness absorbing layer, reducing the effective permittivity of metals via their composition with air, the optimal selection of materials to maximize absorption BW are some examples of these strategies.…”
Section: Light Trapping Schemesmentioning
confidence: 99%
“…[64] In this context, the dielectric function of evaporated Bi nanofilms was shown to present an ideal wavelength dependence to enable a broadband strong absorption with dielectric/Bi nanofilm/dielectric/Ag mirror cavities, in almost the whole visible and near infrared. [65] This suitable wavelength dependence for the dielectric function might be the result of a discontinuous film structure. [66]…”
Section: Visible and Near-infrared Absorptionmentioning
confidence: 99%